Applications of Microbial Enzymes in Industries - Fasiku, Samuel Adedayo; Afolabi, Femi Johnson; Egbeleke, Tawakalit Adeola; Fashogbon, Racheal Oluwayemisi (Darul Yasin Al Sys, 2026)
Microbial enzymes, produced by microorganisms such as bacteria, fungi, and algae, have emerged as indispensable biocatalysts across multiple industrial sectors due to their efficiency, versatility, and activity under diverse environmental conditions. This review aims to highlight the major industrial applications of microbial enzymes and synthesize evidence on their functional roles in contemporary bioprocesses. More than 80 published articles, textbooks, and newsletters were retrieved from reputable platforms, of which approximately 50 were selected for detailed analysis based on relevance and quality. The reviewed literature shows that enzymes now play critical roles in everyday life, with broad applications in medicine, pharmacy, environmental remediation, food processing, detergent manufacture, and energy production. In the detergent industry, amylases, lipases, and proteases are used to break down starch, fats, oils, and proteins, thereby enhancing washing efficiency. In the food sector, microbial enzymes support milk hydrolysis in cheese production, contributing to characteristic flavour development, and are widely employed in fruit juice clarification. In the energy sector, cellulases, xylanases, and lignin-degrading enzymes enable the breakdown of lignocellulosic substrates to release reducing sugars for biofuel production. Medically, L-asparaginase has been used in the treatment of leukaemia, while laccases are applied in the degradation of dyes and the reduction of chemical waste in environmental applications. The diversity of microbial sources allows these enzymes to function under extreme conditions, expanding their usability across varied industrial environments. Overall, the review concludes that microbial enzymes have extensive and growing industrial relevance, underscoring the need for continued research and development to optimize their production, stability, and application in sustainable biotechnological processes.